STATEMENT OF P. GERALD THACKER ACTING COMMISSIONER PUBLIC BUILDINGS SERVICE GENERAL SERVICES ADMINISTRATION BEFORE THE SUBCOMMITTEE ON PUBLIC WORKS AND TRANSPORTATION U.S. HOUSE OF REPRESENTATIVES 19930223 (Tufts Archival Research Center, 2007)
Statement of P. Gerald Thacker of the Public Building Service of the General Services Administration regarding smoking in federal buildings. Describes the Public Building Service. Notes recent evidence on the negative health impacts of secondhand smoke. Argues that existing regulation does not provide enough protection against secondhand smoke. Recommends a complete smoking ban.